A modeler's guide to studying the resilience of social-technical-environmental systems. (1st May 2022) - Tamberg, Lea A; Heitzig, Jobst; Donges, Jonathan F
Abstract: The term 'resilience' is increasingly being used in Earth system science and other disciplines which study what could be called 'social-technical-environmental systems'—systems composed of closely interacting social (e.g. economic and political), technical (e.g. energy production infrastructure), and environmental components (e.g. climate and the biosphere). However, the diversity of resilience theories and a certain (intended) openness of proposed definitions can lead to misunderstandings and may impede their application to complex systems modelling. We propose a guideline that aims to ease communication as well as to support systematic development of research questions and models in the context of resilience. It can be applied independently of the modelling framework or underlying theory of choice. At the heart of this guideline is a checklist consisting of four questions to be answered: (1) Resilience of what? (2) Resilience regarding what? (3) Resilience against what? (4) Resilience how? We refer to the answers to these resilience questions as the 'system', the 'sustainant', the 'adverse influence', and the 'response options'. The term 'sustainant' is a neologism describing the feature of the system (state, structure, function, pathway, …) that should be maintained (or restored quickly enough) in order to call the system resilient. The use of this proposed guideline in the field of Earth system resilience is demonstrated for the application example of a potential climate tipping element: the Amazon rainforest. The example illustrates the diversity of possible answers to the checklist's questions as well as their benefits in structuring the modelling process. The guideline supports the modeler in communicating precisely what is actually meant by 'resilience' in a specific context. This combination of freedom and precision could help to advance the resilience discourse by building a bridge between those demanding unambiguous definitions and those stressing the benefits of generality and flexibility of the resilience concept.